Peningkatan Kompatibilitas Sistem Operasi Windows di Berbagai Perangkat - Rakhmadi Rahman; M Furqan Ramadhanu; Nurul Salsabillah (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2024)
The goal of improving the compatibility of the Windows operating system with various devices is to ensure that Windows runs well on desktops, laptops, tablets, and mobile devices. Technical developments such as system modularization, performance optimization, and better driver integration are part of this effort. To expand the range of devices, Microsoft supports ARM architecture in addition to x86 architecture. Additionally, support for IoT technology, biometric sensors and touch screens has been improved. Maintaining a consistent user experience and expanding the ecosystem of Windows-compatible devices is the goal of this effort.